2022
DOI: 10.3390/math10203889
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Fault Diagnosis Based on Discriminant Analysis Using Multi-View Learning

Abstract: Bearing fault diagnosis has been a challenge in rotating machinery and has gained considerable attention. In order to correctly classify faults, the conventional fault diagnosis methods are mostly based on vibration signals. However, features extracted from a single view of vibration signals may leave out useful information, which can cause the incompleteness of intrinsic information and increase the risk of the performance degradation of fault classifications. In this paper, a novel bearing fault diagnosis me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Discriminant analysis using multi-view learning for bearing fault diagnosis was described in the next paper [11]. FFT, multiview features, and KNN were used for the analysis.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Discriminant analysis using multi-view learning for bearing fault diagnosis was described in the next paper [11]. FFT, multiview features, and KNN were used for the analysis.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Lu et al [29] investigated an effective and reliable deep learning method based on convolutional neural networks (CNN) using cognitive theory to introduce the advantages of image recognition and visual perception into bearing fault diagnosis by simulating the cognitive processes in the cerebral cortex, and the method improved the accuracy of failure mode classification of rolling bearings with respect to environmental noise and fluctuating operating conditions. Tong et al [30] proposed a multi-view learning (DAML)-based bearing fault diagnosis method which obtains a multi-view data set involving vibration and acoustic signals by performing a fast Fourier transform (FFT), and then implements a multi-view feature (MVF) representation including view-invariant information and class discrimination information in a common subspace based on typical correlation analysis (CCA) and uncorrelated linear discriminant analysis (ULDA). The multi-view feature (MVF) representation including view invariant information and class discriminant information is then implemented in a common subspace based on typical correlation analysis (CCA) and uncorrelated linear discriminant analysis (ULDA), and finally a bearing fault is identified using a K-nearest neighbor (KNN) classifier based on the multi-view feature.…”
Section: Status Of Research On Fault Classification and Identificationmentioning
confidence: 99%
“…For example, using dynamic feature extraction along with quadratic discriminant analysis classifier can significantly enhance fault classification and diagnosis in dynamic nonlinear processes, as demonstrated by Li, Jia, and Mao [12]. Furthermore, Tong et al [13] demonstrated the effectiveness of discriminant analysis in their work on bearing fault diagnosis, representing a crucial development in fault diagnosis for dynamic nonlinear processes. For more information on discriminant analysis, see McLachlan [14].…”
Section: Introductionmentioning
confidence: 99%